Collective Bargaining and the Charter: Assessing the Impact of American Judicial Doctrines - Carter, Donald; McIntosh, Thomas (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
This study analyses the impact of American judicial doctrines upon recent Charter decisions relating to Canada's collective bargaining laws. The first section of the paper explores the constitutional foundations of the Canadian and American labour regimes in terms of the fundamental values entrenched in their respective constitutional arrangements. The second section of the paper is an overview of the Charter era labour regime as it has been articulated by the Canadian judiciary and, in particular, by the Supreme Court of Canada. It is the mixed results of this part of the investigation that led us to some tentative conclusions about the impact upon Canadian courts of American judicial influences.